Evaluation of fracture strength of endodontically treated teeth restored by milled zirconia post and core with different post and core systems (An in vitro comparative study) - Huda M Lafta; Adel F Ibraheem (College of Dentistry/ University of Baghdad, 2013)
Background: Restoration of root canal treated teeth with a permanent restoration affect in the success of endodontically treated teeth. This in vitro study was performed to evaluate and compare the fracture strength of endodontically treated teeth restored by using custom made zirconium posts and cores, prefabricated carbon fiber, glass fiber and zirconium ceramic posts. Materials and method: Forty intact human mandibular second premolars were collected for this study and were divided into five groups. Each group contains 8 specimens: Group1: Teeth restored with Carbon Fiber Posts; Group2: Teeth restored with Glass Fiber Posts; Group3: Teeth restored with Zirconium Ceramic prefabricated Posts; Group4: Teeth restored with Zirconium Posts and Cores (copy milling); Group5: (Control Group).For groups 1, 2, 3, and 4; crowns were removed horizontally at the level of cement-enamel junction. Endodontic therapy was then done for all specimens in these groups using step-back technique.These specimens received standardized posts preparation (10mm depth), and then mounted in acrylic resin blocks. Panavia F 2.0 dual cure resin cement was used for cementation. The core build up was done with composite (Filtek P60). The specimens were then stored in saline and were subjected to compressive loads parallel to their long axes using universal testing machine (WP 300) until failure. Results: Data obtained were analyzed by one-way analysis of varianceand student t-test. The results showed that zirconium posts and cores possessed the highest significant differences followed by glass fiber posts, carbon fiber posts, and prefabricated ceramic zirconium posts. There were no significant differences between glass fiber, carbon fiber, and control group. The specimens were examined to determine the root fracture patterns and locations. Conclusion: In the present study the fiber post treated teeth showed significantly more desirable fracture patterns compared to those restored with zircon posts.